Leuprolide and triptorelin treatment in children with idiopathic central precocious puberty: an efficacy/tolerability comparison study - Valenzise, M.; Nasso, C.; Scarfone, A.; Rottura, M.; Cafarella, G.; Pallio, G.; Visalli, G.; Di Prima, E.; Nasso, E.; Squadrito, V.; Wasniewska, M.; Irrera, P.; et al. (Frontiers in Pediatrics, 2023)
Introduction: Central precocious puberty (CPP) results from premature activation of hypothalamic-pituitary-gonadal axis, with the consequent increase of gonadotropin-releasing hormone (GnRH); GnRH agonists (GnRHa) represent the gold-standard therapy in children with CPP although their use might be responsible for pituitary GnRH receptors down-regulation, that in turn suppresses luteinizing hormone (LH) and follicle stimulating hormone (FSH) and blocks of gonadal sex hormones release. The most prescribed GnRHa in the clinical practice are leuprolide and triptorelin, whose use is generally safe and well tolerated; however, mild menopausal-like side effects could appear. The aim of the present study was to investigate and compare the efficacy and tolerability profile of leuprolide and triptorelin in CPP patients. Methods: 110 girls affected by CPP were enrolled in this retrospective study, carried out from 2018 to 2020. The enrolled patients received leuprolide (n=48) or triptorelin (n=62). Efficacy was investigated by the means of clinical parameters and radiological changes and side effects were also recorded to evaluate the possible relationship between the two GnRHa treatments and side effects appearance. Results: At baseline triptorelin patients had significantly higher LH and LH peak levels than leuprolide patients, whereas no significant difference in other patient characteristics was observed between the two groups. The leuprolide treatment lasted 971days [790-1171 days] while the duration of triptorelin administration was 792 days [760-1003 days] (p<0.001). Overall 46 (41,8%) of the studied patients reported mild menopausal-like symptoms: among these 27 were treated with triptorelin and 19 with leuprolide (p=0.558). Patients treated with triptorelin, or leuprolide showed headache (27,4% vs 16,7%), mood swings (12,9% vs 16,7%), increased appetite (12,9% vs 18,8%) and nausea (1,6% vs 10,4%) respectively. Moreover, the onset of side effects appearance related to GnRHa therapy significantly reduces with the increase of the initial bone age (p=0.038). Conclusion: leuprolide and triptorelin treatment appear to be effective and safe without significant difference between the two drugs in term of efficacy and tolerability, making both good options for treating CPP